Estradiol-Treated Female Mice as Surrogate Hosts for Neisseria gonorrhoeae Genital Tract Infections - Jerse, Ann E.; Wu, Hong; Packiam, Mathanraj; Vonck, Rachel A.; Begum, Afrin; Garvin, Lotisha E. (Frontiers in Microbiology, 2011)
Historically, animal modeling of gonorrhea has been hampered by the exclusive adaptation of Neisseria gonorrheae to humans. Genital tract infection can be established in female mice that are treated with 17β-estradiol, however, and many features of experimental murine infection mimic human infection. Here we review the colonization kinetics and host response to experimental murine gonococcal infection, including mouse strain differences and evidence that IL-17 responses, TLR4, and T-regulatory cells play a role in infection. We also discuss the strengths and limitations of the mouse system and the potential of transgenic mice to circumvent host restrictions. Additionally, we review studies with genetically defined mutants that demonstrate a role for sialyltransferase and the MtrC-MtrD-MtrE active efflux pump in evading innate defenses in vivo, but not for several factors hypothesized to protect against the phagocytic respiratory burst and H2O2-producing lactobacilli. Experimental infection of estradiol-treated mice has also revealed the existence of non-host restricted iron sources in the female genital tract and the influence of hormonal factors on colonization kinetics and selection for opacity (Opa) protein expression. Recent work by others with estradiol-treated mice that are transgenic for human carcinoembryonic adhesion molecules (CEACAMs) supports a role for Opa proteins in enhancing cellular attachment and thus reduced shedding of N. gonorrhoeae. Finally we discuss the use of the mouse model in product testing and a recently developed gonorrhea chlamydia coinfection model.